SOLAR TRACKING SYSTEM - Prof. Joshi A.A.; Zuber M. Himone; Anil J. Deshmukh; Sanskar K. Shinde; Nishant M. Waghmare (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
With the rapid depletion of conventional energy sources and the rise in global energy demands, renewable energy technologies have become essential for a sustainable future. Among these, solar energy stands out as an abundant, clean, and renewable resource. However, the fixed positioning of traditional solar panels limits their ability to capture solar radiation efficiently throughout the day. To overcome this limitation, solar tracking systems are developed to improve the overall efficiency of photovoltaic (PV) panels.